Solo - Mansell, Jill (Sourcebooks Landmark, 2017)
It all starts at a party, as these things often do... A one-night stand with far-reaching consequences--Momentarily enamored guests going home with all the wrong people--An unfaithful wife struck by jealousy and getting a dose of her own medicine--A shocking family secret revealed at the worst possible moment... One fling follows another, and now the whole community is embroiled in a great big web of deceit.